IDENTIFICATION OF SENSITIVITY FACTORS OF IC OUTPUT PARAMETERS TO INTERNAL DEFECTS - A. I. Belous; A. V. Prybylski (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The crucial problem of ensuring operational reliability of modern radio electronic equipment is the problem of detecting the integrated circuits with latent (not obvious) defects in the course of production. Such defects shall not be revealed through standard checking procedures specified in standard normative technical documentation.